Man Shabara Dzafira Descriptive Analysis Study of Arabic proverb - Muhamad Syakir; Mohammad Jundurahman; Farhan Fauzaan; Sulthan Arifin Shaqil (Universitas Pendidikan Indonesia, 2022)
Language is an important communication tool in human life, language is used by humans to interact with other people in order to express what they want to convey to others. Each language has its own characteristics, including the peculiarities of the linguistic rules in it. The purpose of this study is to find out how the process of the spread of this proverb to our ears. The method used is a descriptive approach which is to provide a description or description as clearly as possible. The practice of inter-tribal deliberation in the midst of Arab society has become a habit since time immemorial, it is at the time of gathering that ideas, ideas, thoughts begin to form in the community, including proverbs that have benefits that will surely spread among them, to the end of the world. foreign countries including Indonesia through pilgrimage, trade, marriage, and learning meetings conducted by students from the archipelago who returned with a myriad of knowledge, thoughts, ideas, ideas, and including proverbs from the country where he got it, which then disseminated again because of the extraordinary benefits felt. These proverbs are formal language (fusha) which is the highest level in a work of poetry whose position must be proud if someone makes a work using the fusha language.